1996
DOI: 10.1007/bf01575445
|View full text |Cite
|
Sign up to set email alerts
|

The role ofCandida albicans secreted aspartic proteinase in the development of candidoses

Abstract: Although Candida albicans infections in humans are increasingly frequent, our understanding of the host-parasite relationship is limited. The secreted aspartic proteinase of C. albicans was first described in 1965 and has proved to be a major factor in virulence. This enzyme belongs to the class of aspartic proteinases which includes pepsin and renin in humans. Although found in some fungi, secreted aspartic proteinase is rare in these organisms. While the existence of several isoenzymes may not be fully estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
8

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 68 publications
0
39
0
8
Order By: Relevance
“…For more details, the reader is guided to review articles on discovery and characterization of the SAP gene family; structure, processing, activation and regulation; purification, activity and enzymatic properties; and in vitro SAP gene expression in culture medium (50,88,94,95,97,98,145,163,185,227). The present review is restricted to studies addressing the relationship between proteinase production and C. albicans pathogenesis.…”
Section: Candida Sap Familymentioning
confidence: 99%
“…For more details, the reader is guided to review articles on discovery and characterization of the SAP gene family; structure, processing, activation and regulation; purification, activity and enzymatic properties; and in vitro SAP gene expression in culture medium (50,88,94,95,97,98,145,163,185,227). The present review is restricted to studies addressing the relationship between proteinase production and C. albicans pathogenesis.…”
Section: Candida Sap Familymentioning
confidence: 99%
“…For example, Candida is known to have at least seven genes that encode secreted aspartic proteinases (9,33). Aspergilli that cause invasive aspergillosis are known to express genes that encode serine proteinases (34)(35)(36)(37), metalloproteinases (38)(39)(40), and aspartic proteinases (41).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of lines of evidence for their role in pathogenesis, including the correlation between the level of such enzymes and virulence, immunocytochemical evidence for the secretion of the enzyme during infection, protection of the host by inhibition of the enzymes with selective inhibitors or specific antibodies, and enhancement of virulence by gene transfer, have been challenged on the basis of the results of disruption experiments on genes that encode cutinase and cell wall-degrading enzymes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In the case of animal pathogens, single and double proteinase gene disruption failed to show a clear decrease in virulence (15)(16)(17).…”
mentioning
confidence: 99%
“…virulence factors, such as the secreted aspartyl proteases (Sap) (Hoegl et al, 1996 ;Hube et al, 1997 ;, extracellular phospholipases (Ghannoum, 2000), Int1p (Gale et al, 1998) and the outer mannoprotein Hwp1 (Staab et al, 1999), have been identified, and many of these are found either on the cell surface or in the extracellular environment. However, little is known about the means by which these virulenceassociated proteins are processed and secreted.…”
Section: Introductionmentioning
confidence: 99%